Influence of pH and ionic strength on the bulk and interfacial rheology and technofunctional properties of hazelnut meal protein isolate - Gul, Osman; Gul, Latife Betul; Baskıncı, Tugba; Parlak, Mahmut Ekrem; Saricaoglu, Furkan Turker (Elsevier BV, 2023)
The functional, bulk, and interfacial shear rheological properties of hazelnut protein isolate were studied at different pH values between 3.0 and 8.0 and ionic strength levels between 0.0 and 1.0 M. The results showed that pH significantly affected protein solubility, emulsion properties, water and oil holding capacities, foam stability, surface hydrophobicity, and free -SH groups. The highest surface hydrophobicity, free -SH groups, and better functional properties were observed at pH 8.0. Protein solubility also increased with increasing ionic strength up to 0.6 M. The emulsion and foam stability of hazelnut protein isolate showed similar changes with protein solubility. The flow behavior of hazelnut protein suspensions was found to be shear thinning with the highest consistency index at pH 3.0 and the lowest at pH 6.0, however, the ionic strength did not significantly affect the consistency coefficient but did cause a significant change in the flow behavior index, with the lowest value observed at 0.6 M. The best gel structure in hazelnut proteins was observed at pH 3.0 and 4.0. The addition of ions at 0.4 and 0.6 M concentrations resulted in an improved viscoelastic character. The hazelnut protein isolate was also found to form solid-like viscoelastic layers at both air-water and oil-water interfaces, with the interfacial adsorption behavior affected by both pH and ionic strength. Overall, these results suggest that pH and ionic strength have significant effects on the functional and rheological properties of hazelnut protein isolate, which may have the potential as an auxiliary substance in food systems.
Keywords: Corylus; Osmolar Concentration; Proteins; Water; Emulsions; Hydrogen-Ion Concentration; Rheology